Law and Gospel or Gospel and Law? Karl Barth, Martin Luther and John Calvin - Hesselink, I. John (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
For Calvin the order of the law-gospel relation may be put this way: Law of creation (natural law) – revealed law (the law of Moses) – the gospel – the gracious law (third use) as a norm and guide for believers. The same outline would follow for Luther except that the third or positive use of the law plays a minor role in his thinking. On the surface Barth would seem to have more affinity with Calvin but the differences are significant because of Barth’s rejection of any notion of the antithesis of law and gospel and his subsuming the law in all its functions under God’s grace.